System dynamics-based prediction of North Korean port volumes - Tae-Won Chung (Elsevier, 2021)
The purpose of this study is to predict North Korea's cargo volume per port, per item, using system dynamics. The products of which expected volumes are predicted include iron ore, oil, grain, cement, sand, coal, other ores, miscellaneous goods, and containers. We further distribute the forecasted value of each item among the different North Korean ports based on inputs obtained during expert interviews. The selected ports are the nine trading ports of North Korea, namely, Najin, Chongjin, Nampo, Rajin-Seonbong, Songnim, Haeju, Hungnam, Wonsan, and Dancheon. Herein, the authors assume and predict the complete economic reopening of North Korea. Based on the forecast outcomes, Nampo Port handles the largest cargo volume among North Korean ports, which is expected to amount to 113,217 thousand tons by 2050. Chongjin Port is revealed as the second largest in terms of throughput, and is predicted to handle 47,525 thousand tons of cargo by 2050. On the same terms, Najin Port is deemed the third largest and is predicted to handle 37,816 thousand tons of cargo by 2050. Containers (72,454 thousand tons) and cement (45,897 thousand tons) rank first and second among the items of which the largest volumes are expected to be handled by North Korean ports, by 2050. These findings provide insight into North Korean port development potential and indicate prospects for inter-Korean cooperation, following North Korea’s economic reopening.